Precision stellar radial velocity measurements with FIDEOS at the ESO 1-m telescope of La Silla - Vanzi, Leonardo; Zapata, A.; Flores, M.; Brahm, R.; Tala, Marcelo; Rukdee, S.; Jones, M.; Ropert, S.; Shen, T.; Ramirez, S.; Suc, V.; Jordan, A.; et al. (Monthly notices of the Royal Astronomical Society, 2018)
We present results from the commissioning and early science programs of FIDEOS, the new high-resolution echelle spectrograph developed at the Centre of Astro Engineering of Pontificia Universidad Catolica de Chile, and recently installed at the ESO 1m telescope of La Silla. The instrument provides spectral resolution R = 43,000 in the visible spectral range 420-800 nm, reaching a limiting magnitude of 11 in V band. Precision in the measurement of radial velocity is guaranteed by light feeding with an octagonal optical fibre, suitable mechanical isolation, thermal stabilisation, and simultaneous wavelength calibration. Currently the instrument reaches radial velocity stability of = 8 m/s over several consecutive nights of observation.